"An Extraordinarily Pernicious Influence": The Discursive Figure of the Spoiling Grandmother before 1937. (April 2020) - Duschinsky, Robbie; Jacobvitz, Deborah; Peake, Lucy; Messina, Serena
Discourses about the dangers of spoiling children and images of grandparents came together in nineteenth-century literature, with the literary figure of the spoiling grandmother emerging as familiar cultural currency. From there, it would become a concern for the generation of psychoanalysts after Freud, for whom the grandmother represented a dangerous supplement to the importance of the mother for a child's psychological development. The literary and the psychological uses of the figure of the spoiling grandmother then intersected in scientific and popular guidance for parents in the battle for authority regarding the right way to engage in childcare.